Impact of SO2 on Alteration of Reservoir Rock with Ca-Deficient Conditions and Poor Buffering Capacity under a CO2 Geologic Storage Condition. (15th February 2018) - Park, Jinyoung; Choi, Byoung-Young; Jeong, Jong Ok; Shinn, Young Jae
Abstract : The objective of this study is to evaluate the impact of SO2 -CO2 -water-rock interaction on the alteration of a reservoir rock having Ca-deficient conditions and little buffering capacity and its implication for porosity change near the injection well from a CO2 storage pilot site, Republic of Korea. For our study, three cases of experimental and geochemical modeling were carried out (pure CO2, 0.1% SO2 in CO2, and 1% SO2 in CO2, resp.) under realistic geologic storage conditions. Our results show that SO2 accelerated water-rock interactions by lowering the pH. In the 1% SO2 case, pH remained less than 2 during the experiments because of insufficient buffering capacity. Sulfate minerals were not precipitated because of an insufficient supply of Ca. Because the total volume of precipitated secondary minerals was less than that of the dissolved primary minerals, the porosity of rock increased in all cases. Chlorite largely contributed to the decrease in total rock volume although it formed only 4.8 wt.% of the rock. Our study shows that the coinjection of a certain amount of SO2 at CO2 storage reservoirs without carbonate and Ca-rich minerals can significantly increase the porosity by enhancing water-rock interactions. This procedure can be beneficial to CO2 injection under some conditions.